The success rate of artificial insemination in the crossesbred of male Bangkok Chickens and Pelung Hens - Hastuti, Hastuti; Junaedi, Junaedi; Sholikin, Ahmad (Faculty of Animal Science, Universitas Brawijaya, 2021)
Bangkok and Pelung chicken were chickens that are quite popular in Indonesia. One of the breeding programs was to increase meat production could be done through crossbreeding. This study aims to determine the success rate of artificial insemination of crossbreeds of male Bangkok chickens with Pelung hens. The research material used was four male Bangkok chickens aged one year and six female Pelung chickens. This study consisted of four phases: raising chickens, collecting Semen from Bangkok males, artificial insemination of Bangkok males with Pelung hen chickens, and hatching eggs from artificial insemination. The parameters observed in this study were egg weight, fertility, hatchability, DOC weight, and the correlation between egg weight and DOC weight. Data were analyzed using quantitative analysis. The research conducted has obtained an average egg weight of 46.21 grams, 66.67% fertility, 78.57% hatchability of DOC weight 36 grams, and a correlation between egg weight and DOC weight of 0.93%. The research concluded that the results of crossing Bangkok males with Pelung hens could increase hatching egg weight, hatchability, and DOC weight.